Effectiveness of Warm and Cold Compresses To Reduce Pain In Low Back Pain: Literature Review - Ramdhan, Dicki; Zaki Fatarizq, Muhammad; Alif Athallah, Nurawan Nadhir; Nur Alpiah, Dini (International Journal of Social Research, 2024)
Low back pain (LBP) is experienced by almost everyone during their life. The results of research conducted in 14 cities in Indonesia showed that the pain group of the Association of Neurologists throughout Indonesia found 18.13% of sufferers of lower back pain with an average Visual Analog Scale (VAS) value of 5.46 ± 2.56, which means moderate to moderate pain. Severe treatment to deal with LBP effectively can be a solution to patient complaints. Physiotherapists can provide treatment such as warm and cold compress. Literature review research was carried out using the PICO search in the Google Scholar database. There were 5 journals that met the criteria and showed the results that warm and cold compresses carried out with a frequency of 2 times/week, an intensity of 35 degrees Celsius, with a duration of 15 minutes for 6 weeks and carried out 5 times/week, gave better results in relieving pain. and functional activities. Warm and cold compress methods provide significant effectiveness p<0.001 in reducing pain in the lower back.